1989
DOI: 10.1007/bf01538081
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic constipation by colonic dysfunction

Abstract: The personality of two groups of constipated women (by delayed colonic transit or by colonic inertia) was compared to that of two control groups of arthritic patients (rheumatoid or degenerative disease) with the Minnesota Multiphasic Personality Inventory (MMPI). All subjects suffered from chronic pain. Constipated women were found to have significantly higher scores on the hypochondria, hysteria, control, and low back pain scales and a lower score on the masculinity-femininity scale. Discriminant analysis pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(13 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In recent years, scholars have noticed an association between emotional components and intestinal constipation, such as the presence of stress, anorexia, depression, anxiety and hypochondria [34] [35]. Investigating the relation between these emotional symptoms and the microbia imbalance in constipated patients can be subject to oncoming studies.…”
Section: "Gut-brain Axis" and Constipationmentioning
confidence: 99%
“…In recent years, scholars have noticed an association between emotional components and intestinal constipation, such as the presence of stress, anorexia, depression, anxiety and hypochondria [34] [35]. Investigating the relation between these emotional symptoms and the microbia imbalance in constipated patients can be subject to oncoming studies.…”
Section: "Gut-brain Axis" and Constipationmentioning
confidence: 99%
“…In a published series of patients with constipation (27), IBS, and functional abdominal pain (28)(29)(30), there is an excess of women who Effect of Total Abdominal Hysterectomy Y CME Review Article 301 have had hysterectomy. This could be because women with dysfunctional bowel symptoms are more likely to be anxious and polysymptomatic (31)(32)(33). This could also be because women with unexplained lower abdominal pain are often referred to a gynecologist (34,35) who might not consider a bowel origin of the pain until hysterectomy is done (36).…”
Section: Bowel Function After Hysterectomymentioning
confidence: 94%
“…Constipation was shown to be related to previous and current history of disturbed childhood and psychosexual and personality problems [34]and seems to be accessible to behavioural modification [35]. Devroede et al [36]demonstrated a linear relationship between the anxiety/depression scores measured with the MMPI and mean transit time in the ascending colon (fig. 2).…”
Section: Influence Of Psychological Factors On Gut Motilitymentioning
confidence: 99%
“…Correlation between psychological features and colonic motility in 19 patients with IBS. According to Devroede et al [36]. …”
Section: Influence Of Psychological Factors On Gut Motilitymentioning
confidence: 99%